Instructional Design "Postpartum Fitness” for Midwife Staff of Shemiranat (Tehran, Iran) Health Network - Rahmati Roodsari, Rita; Mortazavi, Fathieh; Zar, Abdossaleh (Novelty in Biomedicine, 2018)
Background: One of the postpartum cares lives is supporting and encouraging them more to exercise after delivery and monitoring them. Health care workers, particularly midwives have a great role in the promotion of sport activity. Purpose of this study is Designed training for "postpartum fitness" by Roth well approach for midwives at health network in Shemiranat. Materials and Methods: This research is kind of Instructional design. Sampling was done by using census method Data collection was done by multiple choice tests for knowledge and attitudes of questionnaire and practical assessment exercise was part. After assessment and instructional design and was done Roth well model and Ganyh strategies. Results: Average response to questions in the cognitive domain was 49%. In this study 92% of the employees have positive attitude to importance and impact of the study. The result of the data related to the workplace of participants is health centers (53.3%). Most frequency is for who has less than 5 years’ work experience (50%)and most frequency is for official staff (43.3%), most educational level related to bachelors (83.3%) and the highest age rate is between 30-40 years old (40%). Conclusion: Positive attitude towards this issue and earn score below %80 indicates a need for staff to learn and raise awareness about the above topic. Create knowledge, training, counseling mothers about this issue are the midwife duties. This reflects a greater emphasis on design education.